Evaluation of Ecological Design Principles in Traditional Houses in Mersin - GÜNDOĞDU, EBUBEKİR; BİRER, EMEL (Konya Technical Univ, Fac Architecture & Design, 2021)
Purpose Advances in technology and rapidly developing built environment lead to increased energy consumption and depletion of natural resources while harming the environment. The concept of ecological architecture emerged to generate solutions to these problems and various characteristics of traditional architecture, such as use of local and natural materials, energy saving etc. became important for contemporary ecological architecture. This paper addresses, from an ecological perspective, vernacular traditional architecture in Mersin, which has rapidly grown into a metropole from a 19th century Mediterranean port town. This study focuses on the ecological design components among traditional Mersin houses. The objective of this study is to reveal the relationships between vernacular traditional houses of Mersin and ecological architecture and to serve as a guide and reference for architects to design and construct in a way that they do not harm the natural environment and ecological balance by learning from vernacular architecture. Design/Methodology/Approach For the case study, 30 traditional houses located in Mersin old city centre, have been chosen to be inspected in terms of storey height, structural system, materials used for the construction, roof shape and materials, topography, selection of orientation, vegetation pattern, building form, spatial organisation, building envelope, use of renewable energy sources, sanitary installation and circulation systems. Yes and no scaled checklists were used to assess 30 traditional houses to identify the components of their ecological status and the quantitative data drawn from these checklists were used for the analyses of the urban texture. Findings It is observable from the analysis that traditional vernacular architecture of Mersin has various qualities that are compatible with ecological design criteria of our day. Research Limitations/Implications 30 traditional houses which have not been restored, have been chosen in Mersin old city centre. Originality/Value The results presented in charts and diagrams are aimed to serve as design recommendations in today's architectural practice in the area and as an ecological pattern in sustainable development projects performed in the future.
Keywords: Mersin Traditional Houses; Ecology and Architecture